Influence FF Concentration to Thermal Diffusivity in Liquid Form using Photopyroelectric (PPE) Setup and Dual-Beam Mode-Mismatched Thermal Lens Method with Different Optical Sensors - Ting Lee Mon; Nor Kamilah Sa’at; Raba' Ah Syahidah Azis; Md Shuhazlly Mamat@Mat Nazir; Nur Quratul Aini Ismail (Department of Physics, Sebelas Maret University, 2025)
This study examines the effect of concentration on thermal diffusivity in nano-liquid formulations using the thermal lens method. Standard liquids and nano-liquid samples with varied concentrations were prepared and analyzed. Results showing an average trend of thermal diffusivity by using standard liquids, such as distilled water, ethylene glycol and glycerol and graphene oxide (GO). Thermal lens method with different optical sensors such as PVDF and photodiode also studied to examine the effect of sensor in thermal diffusivity measurement. Results indicate an increase in thermal diffusivity with rising GO concentration up to a threshold, beyond which further increments yield diminishing returns. This behavior is attributed to the unique thermal transport mechanisms enabled by GO nanosheets. These findings offer insights for optimizing GO-based nano-liquids for thermal management applications. Moreover, the study underscores the efficacy of the thermal lens method for probing thermal properties in nanofluid systems.